2020
DOI: 10.1101/2020.11.03.365163
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial structure impacts adaptive therapy by shaping intra-tumoral competition

Abstract: (1) Background: Adaptive therapy aims to tackle cancer drug resistance by leveraging intra-tumoural competition between drug-sensitive and resistant cells. Motivated by promising results in prostate cancer there is growing interest in extending this approach to other cancers. Here we present a theoretical study of intra-tumoural competition during adaptive therapy, to identify under which circumstances it will be superior to aggressive treatment, and how it can be improved through combination treatment; (2) Me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 65 publications
(185 reference statements)
0
30
0
Order By: Relevance
“…Furthermore, the results of Vander Velde et al [65] suggest implementing a continuous phenotype landscape in our model as well as extending our analysis to study combination therapies, strategies for drug combination, and the continued evolution of treatment resistance. Moreover, we do not consider the role of spatial and metabolic heterogeneity [69][70][71], drug infiltration [72,73], nor the role of other cells in the tumour micro-environment [74].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results of Vander Velde et al [65] suggest implementing a continuous phenotype landscape in our model as well as extending our analysis to study combination therapies, strategies for drug combination, and the continued evolution of treatment resistance. Moreover, we do not consider the role of spatial and metabolic heterogeneity [69][70][71], drug infiltration [72,73], nor the role of other cells in the tumour micro-environment [74].…”
Section: Discussionmentioning
confidence: 99%
“…While this assumption of a discrete phenotype landscape simplifies the mathematical modelling, it is not biologically realistic. Moreover, we do not consider the role of spatial and metabolic heterogeneity [56][57][58], drug infiltration [59,60], nor the role of other cells in the tumour micro-environment [61].…”
Section: Discussionmentioning
confidence: 99%
“…Within tumorous tissues and throughout normal tissues, cells compete for space and survival with their neighbors. As recent studies have demonstrated, the spatial structure can shape a tumor's evolution [19,27,28,38]. This spatial competitive aspect has been further experimentally investigated [27,39], but more work needs to be done to better understand how Our analysis of the effects of the distribution of fibroblasts on resistance suggested that there may be an optimal proximity to fibroblasts for maximal tumor cell growth advantage.…”
Section: Discussionmentioning
confidence: 99%
“…In tumors with cells of a varied range of sensitivity, AT resulted in trapping of the resistant cells by the sensitive cells, thus limiting the growth of the tumor [19]. Tumors with spread randomly resistant cells were reported to grow much faster than tumors with resistant cells that were clustered together [27,28]. AT has even been found to delay progression in the absence of fitness costs [27,28], which, however, are assumed to be a key element for the success of AT [12,13].…”
Section: Introduction 19mentioning
confidence: 99%